The cosmology and astrophysics of axion-like particles - Powell, A (2016)
In this thesis I study astrophysical and cosmological effects of axion-like particles (ALPs). ALPs are pseudo-scalar particles, which are generally very weakly-interacting, with a coupling 𝑎/M E · B to electromagnetism. They are predicted by many theories which extend the standard model (SM) of particle physics, most notably string theory. String theory compactifications also predict many scalar fields called moduli which describe the size and shape of the extra, compact dimensions. In string theory models generically the moduli fields are responsible for reheating the universe after inflation. Being gravitationally-coupled, they will also decay to any other particles or sectors of the theory, including any light ALPs, of which there are usually many. The ALPs produced by moduli decay will contribute to dark radiation, additional relativistic energy density. The amount of dark radiation is tightly constrained by observations, this bounds the branching fraction of moduli decays into ALPs, which constrains the string theory model itself. I calculate the amount of dark radiation produced in a model with one light modulus, solely responsible for reheating, called the Large Volume Scenario. I study a minimal version of this model with one ALP and a visible sector comprised of the minimal supersymmetric SM. The dominant visible sector decay mode is to two Higgses, I include radiative corrections to this decay and find that ALP dark radiation is over-produced in this minimal version of the model, effectively ruling it out. The production of ALPs from moduli decay at reheating seems to be a generic feature of string theory models. These ALPs would exist today as a homogeneous cosmic ALP background (CAB). The coupling of ALPs to electromagnetism allows ALPs to convert to photons and vice versa in a magnetic field, leading to potential observable astrophysical signals of this CAB. Observations have shown an excess in soft X-ray emission from many galaxy clusters. I use detailed simulations of galaxy cluster magnetic fields to show that a CAB can explain these observations by conversion of ALPs into X-ray photons. I simulate ALP–photon conversion in four galaxy clusters and compare to soft X-ray observations. I show the excesses (or lack thereof) can be fit consistently across the clusters for a CAB with ALP–photon inverse coupling of M = 6 − 12 × 1012 GeV, if the CAB spectrum has energy ∼ 200 eV. I also study the possibility of using galaxy clusters to search for and constrain the ALP coupling to photons using cluster X-ray emission. Conversion of X-ray photons into ALPs will cause spectral distortions to the thermal X-ray spectrum emitted by galaxy clusters. I show that the non-observation of these distortions is able to produce the strongest constraints to date on the ALP–photon inverse coupling, M ≳ 7 × 1011 GeV.